Ordinance No. 78: An Ordinance as to Retailing Gunpowder, in L.A. Civill, Charter of the City of Louisville, Ky.: Part Third, Ordinances of the City of Louisville 55 (1862) (enacted 1853) - (:unkn) unknown (My University, 1853)
Prohibited the sale of gunpowder to minors under 15 years of age, "free colored persons," or "slaves" without permission from a parent, guardian, or master.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES; TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER - MINORS